Controls on methane released through ebullition in peatlands affected by permafrost degradation. Issue 3 (28th March 2014) - Klapstein, Sara J.; Turetsky, Merritt R.; McGuire, A. David; Harden, Jennifer W.; Czimczik, Claudia I.; Xu, Xiaomei; Chanton, Jeffrey P.; Waddington, James M.
Abstract Permafrost thaw in peat plateaus leads to the flooding of surface soils and the formation of collapse scar bogs, which have the potential to be large emitters of methane (CH4) from surface peat as well as deeper, previously frozen, permafrost carbon (C). We used a network of bubble traps, permanently installed 20 cm and 60 cm beneath the moss surface, to examine controls on ebullition from three collapse bogs in interior Alaska. Overall, ebullition was dominated by episodic events that were associated with changes in atmospheric pressure, and ebullition was mainly a surface process regulated by both seasonal ice dynamics and plant phenology. The majority (>90%) of ebullition occurred in surface peat layers, with little bubble production in deeper peat. During periods of peak plant biomass, bubbles contained acetate‐derived CH4 dominated (>90%) by modern C fixed from the atmosphere following permafrost thaw. Post‐senescence, the contribution of CH4 derived from thawing permafrost C was more variable and accounted for up to 22% (on average 7%), in the most recently thawed site. Thus, the formation of thermokarst features resulting from permafrost thaw in peatlands stimulates ebullition and CH4 release both by creating flooded surface conditions conducive to CH4 production and bubbling as well as by exposing thawing permafrost C to mineralization.